PERSEPSI PENGGUNA TERHADAP SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) TERKAIT SENSUS HARIAN RAWAT INAP RUMAH SAKIT UMUM DAERAH KOTA YOGYAKARTA - , ASTRI DEWI APRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Inpatient daily census in RSUD Yogyakarta done by a nurse in a treatment room manually. Although the menu daily inpatient census was found in SIMRS but not optimally utilized for the implementation constraints are found, that is daily inpatient census mismatch manual with daily inpatient census is in SIMRS. This is possible due to the human factor. Therefore, it is necessary to evaluate the human resources as the user in the implementation of Hospital Management Information System related hospital inpatient daily census in Local Government General Hospital Yogyakarta. Goal: To knowing the user perception in implementing management information system-related hospital inpatient daily census in Local Government General Hospital Yogyakarta. Method: This type of research is descriptive qualitative approach. The study design was cross-sectional. Data collection techniques in this study were interviews, observation, and study documentation. Result: Daily census of inpatient treatment in Yogyakarta in-RSUD first input by the staff in computerized inpatient register through SIMRS, then the nurses make SHRI manually and then submitted to the Installation Medical Record to be processed. Daily census of inpatient treatment not in accordance with the procedures contained in the SOP job or Procedures RSUD Yogyakarta. SIMRS related SHRI in RSUD Yogyakarta useful to users because make work more quickly, useful, enchance effectiveness, improve job performance, and makes job easier. However, for productivity and employment hasnât increased due to the relatively fixed data quality doesnât match the quality of real data so it canât be a reference data. SIMRS related SHRI in RSUD Yogyakarta makes it easy for users because it is easy to learn, easy to use, easy to become skillful, and flexible. However, for the indicator clear and understandable controllable and canât be fulfilled because of the absence of a policy regarding the return flow inpatients correct. The attitude of the user of the Hospital Management Information System in Yogyakarta City Hospital has been rated good and the users want to use. But the Hospital Management Information System related inpatient daily census has not been enough to satisfy users. Interest in user behavior Hospital Management Information System related daily census of inpatient hospital Yogyakarta that want to follow training on SIMRS.